Neutron based archaeometallurgical investigation of Picenan and Roman age metal objects from the Academia Georgica Treiensis collection (Italy). Issue 2 (15th December 2017) - Rogante, M.; Rosta, L.; Káli, Gy.; Kasztovszky, Zs.; Kis, Z.; Kovács, I.; Maróti, B.; Szőkefalvi-Nagy, Z.
ABSTRACT: Non-destructive prompt gamma activation analysis (PGAA), neutron radiography (NR) and high resolution time-of-flight neutron diffraction (TOF-ND) have been applied to investigate metal archaeological artefacts belonging to the Academia Georgica Treiensis ( AGT ) collection. 8 archaeological items have been analysed, by using the facilities of the Budapest Neutron Centre (BNC). Some of these objects mostly dating back probably to the VI-IV century B.C. and presumed to be discovered in the Marche Region, Italy. The primary goal of the analyses was to advance the correct technological and material description of the objects, providing scientific data for further and more comprehensive comparative analyses also covering the find material from the close archaeological sites. The neutron investigations allowed determining the bulk composition, also providing either a qualitative and quantitative assessment of the phase composition and the structural properties of the constituents, or radiographic images, which would finally help to identify possible manufacturing techniques. Additional examinations, carried out by external milli-beam particle induced X-ray emission spectroscopy (PIXE), provided quantitative analyses of major and trace elements (e.g., Fe, Pb and As) in order to recognize the constitutive alloys and to supply information on the near-surface elemental composition, complementary to the data characteristic for the bulk. The obtained results, thought to be useful to set up a classification according to the chemical composition, and this way allow achieving important information related to the possible provenance of the objects.